Investigation on strength of fiber reinforced clay - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2011)
Clay soils and their related behavior has always been the subject of many studies. Recent researches show some interests in investigation of inclusion of randomly distributed fiber in clay. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of fiber inclusion on the strength of subgrade material. Natural fiber was used for this investigation. Fiber contents and length have been changed during these tests. The fiber percentage varied from 0 % (for unreinforced samples) to 3% and fiber length varied from 15mm to 65mm. In addition, as the other alternative 0.5% cement material was put in fiber composite to see the performance of composite. Clay was selected as soil. Triaxial Consolidated Undrained (CU) compression tests were carried out to investigate behavior of the composite under different condition. The fiber length and fiber content found to play important rule on the strength of fiber reinforced composite. Furthermore it was observed that ductility of sample increased by fiber inclusion. Cement percentage also found to be a good tool to stabilize soil composite. (2011) Trans Tech Publications, Switzerland.